Role of GFI1 in Epigenetic Regulation of MDS and AML Pathogenesis: Mechanisms and Therapeutic Implications - Möröy, Tarik; Khandanpour, Cyrus (Frontiers in Oncology, 2019)
Growth factor independence 1 (GFI1) is known as a DNA binding zinc finger protein which can mediate transcriptional repression mainly by recruiting histone-modifying enzymes to its target genes. GFI1 plays important roles in hematopoiesis, in particular in regulating the function of hematopoietic stem- and precursor cells and the differentiation along myeloid and lymphoid lineages. In recent years, a number of publications provided evidence that GFI1 is involved in the pathogenesis of both acute myeloid leukemia (AML) and its proposed precursor stage, the myelodysplastic syndrome (MDS), and possibly also in the progression from MDS to AML. For instance, expression levels of the GFI1 gene correlate with patient survival and treatment response in both AML and MDS and can influence disease progression and maintenance in experimental animal models. Also, a non-synonymous single nucleotide polymorphism (SNP) of GFI1, denominated GFI1-36N, which encodes a variant GFI1 protein with a decreased efficiency to act as a transcriptional repressor was found to be linked to AML and MDS and to be a prognostic factor for these diseases. Similar to the presence of the GFI1-36N variant, reduced expression of the GFI1 gene can lead to genome-wide epigenetic changes at sites where GFI1 occupies target gene promoters or enhancers. Of interest, these epigenetic changes affect the response of leukemic cells to epigenetic drugs such as HDAC- or HAT inhibitors indicating that GFI1 expression levels and genetic variants of GFI1 are of clinical relevance. Based on these and other findings, individual groups have proposed specific therapeutic approaches to treat AML by targeting epigenetic changes that occur as a consequence the state of GFI1. Here, we will give an overview with regard to the well-known role of Gfi1 as a transcription factor, but also include the more recently discovered functions of GFI1 that are independent of DNA binding and how they may affect disease progression and the choice of epigenetic drugs for therapeutic regimens of AML and MDS.